Preparation, Physicochemical Properties, and In Vitro Toxicity towards Cancer Cells of Novel Types of Arsonoliposomes - Paraskevi Zagana; Spyridon Mourtas; Anastasia Basta; Sophia G. Antimisiaris (MDPI AG, 2020)
Arsonoliposomes (ARSL) are liposomes that incorporate arsonolipids (ARS) in their membranes. They have demonstrated significant toxicity towards cancer cells, while being less toxic towards normal cells. In this study, we sought to investigate the possibility to prepare novel types of arsonoliposomes (ARSL) by incorporating a lipidic derivative of curcumin (TREG) in their membrane, and/or by loading the vesicles with doxorubicin (DOX). The final aim of our studies is to develop novel types of ARSL with improved pharmacokinetics/targeting potential and anticancer activity. TREG was incorporated in ARSL and their integrity during incubation in buffer and serum proteins was studied by monitoring calcein latency. After evaluation of TREG-ARSL stability, the potential to load DOX into ARSL and TREG-ARSL, using the active loading protocol, was studied. Loading was performed at two temperatures (40 °C and 60 °C) and different time periods of co-incubation (of empty vesicles with DOX). Calculation of DOX entrapment efficiency (%) was based on initial and final drug/lipid ratios. The cytotoxic activity of DOX-ARSL was tested towards B16F10 cells (mouse melanoma cells), LLC (Lewis Lung carcinoma cells), and HEK-293 (Human embryonic kidney cells). Results show that TREG-ARSL have slightly larger size but similar surface charge with ARSL and that they are both highly stable during storage at 4 °C for 56 d. Interestingly, the inclusion of TREG in ARSL conferred increased stability to the vesicles towards disruptive effects of serum proteins. The active-loading protocol succeeded to encapsulate high amounts of DOX into ARSL as well as TREG-LIP and TREG-ARSL, while the release profile of DOX from the novel liposome types was similar to that demonstrated by DOX-LIP. The cytotoxicity study results are particularly encouraging, since DOX-ARSL were less toxic towards the (normal) HEK cells compared to the two cancer cell-types. Furthermore, DOX-ARSL demonstrated lower toxicities (at all concentrations tested) for HEK cells, compared to that of the corresponding mixtures of free DOX and empty ARSL, while the opposite was true for the cancer cells (in most cases). The current results justify further in vivo exploitation of DOX-ARSL, as well as TREGARSL as anticancer therapeutic systems.